The Isotope Hydrology of a Large River System Regulated for Hydropower. (4th March 2014) - Soulsby, C.; Birkel, C.; Geris, J.; Tetzlaff, D.
Abstract Impoundments, regulation and inter‐basin transfers associated with large hydropower developments affect runoff regimes, water residence times and stream water quality. We used stable isotopes to understand these effects on the river Tay system in Scotland, examining their spatial and temporal variation in surface waters at 22 sites. Spatial patterns of isotopes in stream water were consistent with those of precipitation, being more depleted in streams draining higher, colder northern headwaters and enriched in the milder western headwaters. To a lesser extent, spatial patterns also reflected effects of inter‐basin and intra‐basin water transfers at some sites. Temporal dynamics reflected precipitation inputs modulated by landscape properties, the presence of lakes and reservoirs, and regulation operations. Isotopic variability was highest in headwater tributaries with responsive soils and lowest downstream of lakes and reservoirs. Variability of isotopes in lower river sites was also damped as they integrate contributions from the rest of the catchment. Importantly, regulation from both reservoirs and inter‐basin transfers can distort simple input–output relationships for stable isotopes and affect catchment transit times with implications for water quality and in‐stream ecology. On the one hand, reservoirs and extension of natural lakes have created additional storage, potentially slowing flows; on the other, transfers have increased the volume and rates of water throughput in many of these water bodies, reducing hydraulic turnover times. Such effects tend to be quite localized and are not apparent at the larger catchment scale. Copyright © 2014 John Wiley & Sons, Ltd.